Therapeutic approach to pediatric acute mastoiditis – an update - Mierzwiński,Józef (2019)
Abstract Introduction: Acute mastoiditis remains the most common complication of acute otitis media. It may rarely appear also in cochlear implant patients. However, the treatment recommendations for this disease are not precisely defined or employed, and in the current literature the differences regarding both the diagnosis and management are relatively substantial. Objective: The aim of this study was to determine a standard and safe procedure to be applied in case of pediatric acute mastoiditis. Methods: A retrospective chart review of 73 patients with 83 episodes of acute mastoiditis hospitalized at our tertiary-care center between 2001 and 2016 was conducted. Bacteriology, methods of treatment, hospital course, complications, and otologic history were analyzed. Based on our experience and literature data, a protocol was established in order to standardize management of pediatric acute mastoiditis. Results: All the patients treated for acute mastoiditis were submitted to an intravenous antibiotic regimen. In the analyzed group pharmacological treatment only was applied in 11% of children, in 12% myringotomy/tympanostomy was added, and in the vast majority of patients (77%) mastoidectomy was performed. In our study recurrent mastoiditis was noted in 8% of the patients. We also experienced acute mastoiditis in a cochlear implant child, and in this case, a minimal surgical procedure, in order to protect the device, was recommended. Conclusions: The main points of the management protocol are: initiate a broad-spectrum intravenous antibiotic treatment; mastoidectomy should be performed if the infection fails to be controlled after 48 h of administering intravenous antibiotic therapy. We believe that early mastoidectomy prevents serious complications, and our initial observation is that by performing broad mastoidectomy with posterior attic and facial recess exposure, recurrence of acute mastoiditis can be prevented.